2010
DOI: 10.1016/j.jacc.2010.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Level of Adenosine Diphosphate Receptor P2Y12 Blockade During Percutaneous Coronary Intervention Predicts the Extent of Endothelial Injury, Assessed by Circulating Endothelial Cell Measurement

Abstract: Optimal ADP receptor P2Y(12) blockade reduces the endothelial injury during PCI. This protective effect of clopidogrel on endothelial cells could add to the clinical benefit associated with this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In contrast to the reduced levels of EPCs in chronic vascular conditions, levels of EPCs increase following acute vascular injury and/or tissue ischemia [1,5,6]. Prior studies have demonstrated that even a focal and limited endothelial injury, such as that caused by PCI with stent placement, induces a rapid rise in the level of circulating EPCs, peaking at 6-12 h after the procedure [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the reduced levels of EPCs in chronic vascular conditions, levels of EPCs increase following acute vascular injury and/or tissue ischemia [1,5,6]. Prior studies have demonstrated that even a focal and limited endothelial injury, such as that caused by PCI with stent placement, induces a rapid rise in the level of circulating EPCs, peaking at 6-12 h after the procedure [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicate that circulating endothelial progenitor cells (EPCs), a population of bone marrow-derived cells, have an important role in the process of vascular repair, by promoting reendothelization following injury [1][2][3]. Furthermore, levels of EPCs increase following vascular injury and/or tissue ischemia, for example after percutaneous coronary intervention (PCI) [4][5][6][7]. A major goal of adjunctive therapy given during and after PCI is to minimize the extent of vascular injury, and promote the repair process of the damaged endothelial layer.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Journal, Bonello et al (10) deal with an interesting topic on response variability to clopidogrel as a determinant of the magnitude of endothelial injury after PCI. Endothelial injury and loss of vascular integrity, in general, is a crucial factor for the initiation and progression of atherosclerosis, as well as a key trigger for atherothrombosis.…”
Section: See Page 1024mentioning
confidence: 99%
“…Levels of CD34 + KDR + EPCs are inversely correlated with cardiovascular risk factors, and are predictive of cardiovascular outcome in patients with coronary artery disease (CAD) [16,17]. Animal studies demonstrated a role for circulating EPCs in endothelial repair [11][12][13][14][15][16][17][18][19][20]. Furthermore, preliminary findings in humans suggest that bone marrow-derived progenitor cells can be mobilized in response to coronary stenting in stable CAD patients and may be linked to intimal hyperplasia [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%